2016
DOI: 10.1093/occmed/kqw141
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence among peer-supported drivers after occupational trauma

Abstract: Severe and fatal PTEs had the strongest impact on sickness absence after PTEs. For less severe PTE, peer support provided by colleagues may be superior to supervisor support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In a prospective cohort study, Carleton et al [ 33 ] reported short-lived, small, but statistically significant improvements in stigma following the Road to Mental Readiness training program, but no statistically significant improvements in mental health. The two retrospective cohort studies [ 34 , 36 ] examined sick days as an outcome measure, while one study [ 38 ] examined suicide rates. Again, all studies reported favorable results, with varying quality of research and strength of evidence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective cohort study, Carleton et al [ 33 ] reported short-lived, small, but statistically significant improvements in stigma following the Road to Mental Readiness training program, but no statistically significant improvements in mental health. The two retrospective cohort studies [ 34 , 36 ] examined sick days as an outcome measure, while one study [ 38 ] examined suicide rates. Again, all studies reported favorable results, with varying quality of research and strength of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…All of the 14 studies received at least one high risk or unclear rating on the strength of evidence criteria. One study was rated moderate to high quality [ 35 ], nine studies were of moderate to low quality [ 27 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 ], and four studies were of low quality [ 28 , 29 , 30 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a cumulative effect when train drivers are confronted with more than one CI and the impact of these incidents adds up. 3,5,15,17,[19][20][21] Train drivers may also lose their concentration and motivation and simply wait around for retirement. 2 Additionally, when train drivers experience lack of meaning in life, loss of selfefficacy, feelings of failure, loss of control, or a sense of alienation or guilt following the CI, traumatic impacts have increased intensity and duration.…”
Section: Personal Experiencesmentioning
confidence: 99%
“…Most train drivers recover from CIs, but at different speeds. 17,18 It is important to identify factors that facilitate and hinder recovery in order to develop adequate support strategies. Prior studies have identified some risk and protective factors that are associated with the likelihood, extent, and speed of recovery:…”
mentioning
confidence: 99%